LEGAL PROTECTION OF ONLINE SOCIAL GATHERING MEMBERS EXPERIENCE LOSSES DUE TO DEFENSE - Baharudin Saleh Ingratubun (Faculty of Law, Universitas Pekalongan, 2022)
This research aims to determine legal protection for online social gathering participants and also to determine inhibiting factors in dealing with members who are in default. The type of research used is sociological legal research or empirical law. Empirical legal research is legal research that analyzes the actual application of law to individuals, groups, communities, legal institutions in society with an emphasis on the behavior of individuals or communities, organizations or legal institutions in relation to the application or enactment of the law. In this research, the author conducted research in Jayapura City as the author discovered problems in the field regarding the rights of owners who were disadvantaged in transactions via electronic media at online social gatherings. The research results show that the legal protection that is expected to be provided to members who experience losses is legal protection related to compensation. However, in order to get the entire compensation, the management found obstacles in it, namely the online social gathering manager could not provide proof because there was no guarantee or written agreement in it. Inhibiting factors in dealing with members who are in default are: Settlement of default cases committed by one party against another party can initially be pursued in a non-litigation manner before ultimately if a settlement is not reached then it will be continued in litigation or before trial.